Two new species of Scheloribatidae (Acari, Oribatida) from Costa Rica - Ermilov, Sergey G. (2015)
Two new species of oribatid mites of the family Scheloribatidae, Scheloribates costaricensis sp. nov. and Perscheloribates paraluminosus sp. nov., are described from leaf litter of secondary forest in Costa Rica. Scheloribates costaricensis sp. nov. is most similar morphologically to Scheloribates brasilosphericus Badejo, Woas & Beck, 2002, however, it differs from the latter by morphology of bothridial and adoral setae, length of prodorsal setae, body surface, structure of antero-ventral part of leg femora, and the presence of large tubercle on posterior margin of notogaster and well visible dorsal notogastral setae. Perscheloribates paraluminosus sp. nov. is most similar morphologically to Perscheloribates luminosus (Hammer, 1961), however, it differs from the latter by body length and color, structure of rostrum, length of rudimentary parts of translamellar line, and the presence of two longitudinal furrows in anogenital region.